Growth, maturity, and diet of the pearl whipray (Fontitrygon margaritella) from the Bijagós Archipelago, Guinea-Bissau - Owen N. Clements; Guido Leurs; Rob Witbaard; Ido Pen; Yvonne I. Verkuil; Laura L. Govers (PeerJ, 2022)
The pearl whipray Fontitrygon margaritella (Compagno & Roberts, 1984) is a common elasmobranch in coastal western African waters. However, knowledge on their life-history and trophic ecology remains limited. Therefore, we aimed to determine the growth, maturity and diet of F. margaritella from the Bijagós Archipelago in Guinea-Bissau. Growth was modelled with: von Bertalanffy, Gompertz and logistic functions. Model selection revealed no model significantly outperformed another. The sampled age ranged from less than 1 to 7 years (1.8 ± 1.9 cm, mean ± standard deviation) and size (disc width) ranged from 12.2 to 30.6 cm (18.7 ± 5.2 cm). Size-at-maturity was estimated at 20.3 cm (95% CI [18.8–21.8 cm]) for males and 24.3 cm for females (95% CI [21.9–26.5 cm]), corresponding ages of 2.2 and 3.9 years. The diet differed significantly among young-of-the-year (YOY), juveniles and adults (p = 0.001). Diet of all life stages consisted mainly of crustaceans (27.4%, 28.5%, 33.3%) and polychaetes (12.5%, 26.7%, 20.3%), for YOY, juveniles and adults respectively. This study shows that F. margaritella is relatively fast-growing, matures early and experiences ontogenetic diet shifts. These results contribute to status assessments and conservation efforts of F. margaritella and closely related species.